Contact sport related head and neck injuries in pediatric athletes. (June 2019) - Scheffler, Patrick; Wolter, Nikolaus E.; Namavarian, Amirpouyan; Propst, Evan J.; Chan, Yvonne
Abstract: Objectives: To describe the type and frequency of sports related pediatric head and neck trauma. Methods: The National Electronic Injury Surveillance System (NEISS) was searched for football, basketball, soccer, lacrosse and ice hockey related facial injuries. Cross-sectional analysis of incidence, age, and sex and specific injury diagnoses, mechanisms, and facial locations were performed. We focused on craniofacial and soft tissue injuries and excluded patients with concussion or other neurological injuries. Results: A total of 24, 905 cases were identified in the NEISS database, corresponding to an estimated, 764, 293 emergency department visits. The most hazardous sports were basketball, accounting for 356, 188 visits (46.6%), football with 249, 633 visits (32.6%), and soccer with 128, 113 (14.7%) visits. Lacrosse and ice hockey accounted for 16, 869 (1.9%) and 13, 490 (1.5%) visits, respectively. There has been a decrease in injuries over the past 10 years, particularly for football (53%), ice hockey (46%), and lacrosse (41%). Soccer (13%) and basketball (9%) noticed the smallest decreases. Conclusion: Children who play basketball, football and soccer are especially prone to emergency department visits related to the head and neck. Overall, there has been an improvement in number of injuries across the five sports investigated. Sports amenable to head and neck protective equipment saw the largest improvement (football, ice hockey, lacrosse), whereas only small decreases were noted in basketball and soccer. Changes in regulations for sports not amenable to more protective equipment may help decrease adverse events.